Explore the soil factors driving soil microbial community and structure in Songnen alkaline salt degraded grassland - Bai, Zhenyin; Jia, Aomei; Li, Haixian; Wang, Mingjun; Qu, Shanmin (Frontiers in Plant Science, 2023)
Introduction Saline-alkali degradation in grassland significantly affects plant community composition and soil physical and chemical properties. However, it remains unclear whether different degradation gradients affect soil microbial community and the main soil driving factors. Therefore, it is important to elucidate the effects of saline-alkali degradation on soil microbial community and the soil factors affecting soil microbial community in order to develop effective solutions to restore the degraded grassland ecosystem. Methods In this study, Illumina high-throughput sequencing technology was used to study the effects of different saline-alkali degradation gradients on soil microbial diversity and composition. Three different gradients were qualitatively selected, which were the light degradation gradient (LD), the moderate degradation gradient (MD) and the severe degradation gradient (SD). Results The results showed that salt and alkali degradation decreased the diversity of soil bacterial and fungal communities, and changed the composition of bacterial and fungal communities. Different degradation gradients had different adaptability and tolerance species. With the deterioration of salinity in grassland, the relative abundance of Actinobacteriota and Chytridiomycota showed a decreasing trend. EC, pH and AP were the main drivers of soil bacterial community composition, while EC, pH and SOC were the main drivers of soil fungal community composition. Different microorganisms are affected by different soil properties. The changes of plant community and soil environment are the main factors limiting the diversity and composition of soil microbial community. Discussion The results show that saline-alkali degradation of grassland has a negative effect on microbial biodiversity, so it is important to develop effective solutions to restore degraded grassland to maintain biodiversity and ecosystem function.